Prevalensi Penyakit Ginjal Stadium Akhir dengan Penyakit Kardiovaskular, Diabetes Mellitus, dan Anemia - Aini, Nauvila Fitrotul; Nursalam, Nursalam; Widyawati, Ika Yuni (Journal of Telenursing (JOTING), 2023)
This study aims to describe the prevalence of end-stage kidney disease with complications of heart and blood vessel disease, diabetes mellitus, and anemia. The design of this study is cross-sectional, in which the researcher wishes to describe the prevalence in patients with end-stage kidney disease and determine the relationship between the characteristics of respondents and complications in end-stage kidney disease. The population in this study were medical records of patients with end-stage kidney disease at a hospital in East Java from January 2022 - August 2022. The sample in this study consisted of 101 medical records. Data analysis used descriptive analysis and a chi-square test. The results showed that there is a relationship between gender and complications of diabetes mellitus (0.045), gender and complications of anemia (0.01), and work and the incidence of complications of anemia (0.008) in patients with end-stage kidney disease. This study concludes that most cases of complications experienced by end-stage kidney patients were heart and blood vessel disease. Keywords: CKD, End Stage Kidney Disease, Nursing.